2017
DOI: 10.1177/0956462417696215
|View full text |Cite
|
Sign up to set email alerts
|

Generic substitution of antiretrovirals: patients’ and health care providers’ opinions

Abstract: There is interest in introducing generic antiretroviral drugs (ARVs) into high-income countries in order to maximise efficiency in health care budgets. Studies examining patients’ and providers’ knowledge and attitudes to generic substitution in HIV are few. This was a cross-sectional, observational study with a convenience sample of adult HIV-infected patients and health care providers (HCPs). Data on demographics, knowledge of generic medicine and facilitators of generic substitution were collected. Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…The use of generic ARV drugs may offer one potential route for controlling rising costs while maintaining quality of care. We identified no voiced concerns regarding generic drug use, safety or efficacy, contrasting with concerns regarding generic drugs expressed elsewhere [28,29], and found that acceptability was similar to that in other reports [22,33]. Although the study was not randomized, we could find no signal of decreased antiviral efficacy or intolerances in those choosing gK/T.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The use of generic ARV drugs may offer one potential route for controlling rising costs while maintaining quality of care. We identified no voiced concerns regarding generic drug use, safety or efficacy, contrasting with concerns regarding generic drugs expressed elsewhere [28,29], and found that acceptability was similar to that in other reports [22,33]. Although the study was not randomized, we could find no signal of decreased antiviral efficacy or intolerances in those choosing gK/T.…”
Section: Discussionmentioning
confidence: 52%
“…Walensky et al [18] projected a potential saving of > US$1 billion from de-simplifying one commonly used branded STF regimen. However, diverse concerns of both physicians and patients about the efficacy of generic drugs, the increase in pill burden, the risk of switching successful regimens, and patient acceptability may impact the uptake and use of generic ART [25][26][27][28][29][30][31][32][33][34]. Increasing pill burden may be seen as a step back [35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both patients and prescribers are open-minded and willing to share generic medicines [52]. Coincidentally, in two studies, about half of the patients, Engelhard et al [56] and Krentz et al [57] declared their consent to an exchange of elements of their cART even with a higher number of tablets, if the advantage would not only be theirs but a cost saving for their health insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the special requirements for consistent compatibility and effectiveness of cART, a continuing controversy concerns the safety of a substance exchange even in the case of generics with identical active ingredients [50][51][52]. Some studies have described risks for sustainability of virological control by cART when the generic drug was associated with a higher number of pills [50,53].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, changing branded STRs for their equivalent generic components often entails administering them as at least two separate pills (these changes are known as “de‐simplifying STRs” or “breaking the combos”). These changes are controversial, and several studies have shown that, while most HIV care clinicians agree on using generic ARVs to decrease healthcare costs, many of them do not agree to de‐simplify STRs, mainly because of concerns of potential decreased treatment adherence [ 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%